A Hypothetical Protein Fragment from Large Yellow Croaker (Larimichthys crocea) Demonstrates Significant Activity Against Both Bacterial and Parasite - Chunmei Yan; Meiling Chen; Hao Xu; Jian Jin; Xiande Liu; Zhiyong Wang; Dongling Zhang (Fishes, 2025)
Antimicrobial peptides (AMPs) are biocompatible and biodegradable, making them an attractive alternative to traditional antimicrobial agents and chemical preservatives. Here, a novel α-helix amphiphilic anionic AMP Lc149 was screened from a large yellow croaker (Larimichthys crocea) using a Bacillus subtilis expression system. Lc149 is a hypothesized protein fragment not annotated in the genome of a large yellow croaker. Both extracellular protein and recombinant Lc149 (rLc149) exhibited significant killing effects against Gram-negative Escherichia coli and Vibrio harveyi. Scanning and transmission electron microscopy revealed that rLc149 had the ability to disrupt bacterial cell membranes, causing irregular cell morphology, severe cell membrane damage, cytoplasm agglutination, and intracellular content leakage. Confocal laser scanning microscopy and flow cytometry further confirmed bacterial cell destruction and mortality rates of over 80%. Gel retardation assays and SDS-PAGE electrophoresis showed that rLc149 was unable to bind to bacterial DNA, but did reduce bacterial protein contents. Additionally, rLc149 maintained antibacterial activity against E. coli and V. harveyi upon exposure to temperatures of 25–100 °C, UV radiation time of 0–60 min, pH levels of 3–12, and different proteases. Biosafety assays revealed low hemolytic toxicity to erythrocytes of large yellow croaker, rabbit, and shrimp, and low cytotoxicity to large yellow croaker kidney cells and HEK 293T cells. More deeply, rLc149 also possessed significant killing activity against parasites. Therefore, rLc149 can be considered an antibacterial and antiparasitic drug in fisheries.